IMPLIKATUR PERCAKAPAN MAHASISWA STKIP MUHAMMADIYAH PRINGSEWU LAMPUNG - Fitriyani, Dwi (JURNAL PESONA, 2016)
This research is pragmatic study which investigate conversational implicature of students of STKIP Muhammadiyah Pringsewu, Lampung. This study is aimed to investigate type and function of studentsâ conversational implicature. The researcher used pramatic-in-dividing. The indicator is inter locutor. In collecting the data, the researcher used recording, observation, and writing technique. In analysing the data, the researcher recorded the source data, observed, wrote, and examined the conversation which is related to type and function of impilacture. The result indicated that many students of STKIP Muhammadiyah Pringsewu, Lampung used non-conventional implicature. While the conversational implicature function that students used was communicative and informative.Keywords: conversational implicature, students, Pringsewu, and pragmatic.